Use Of Innovative Methods of Teaching Physics in Modern Educational Institutions - Qodirov.M.Q; Qosimov.B.O (Genius Journals, 2022)
The article discusses some aspects of using innovative methods, pedagogy, computer technologies, and the latest achievements of science in teaching natural sciences, especially physics, in modern educational institutions.
Keywords: Thinking; competence; knowledge; education